(untitled) (Journal of the College of Basic Education, 2022)
In this research study the efficiency of silicon solar cell has been enhanced after coated with polymer composite from ((cyanoacrlate)) doped with (0.002) gm R6G.The efficiency increased from (6.2 %) to (14.7%) because of increase in intensity absorbed.